2000
DOI: 10.1046/j.1469-8137.2000.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi might alleviate aluminium toxicity in banana plants

Abstract: Some mycorrhizal plants exhibit greater resistance than nonmycorrhizal plants to aluminium toxicity. This has not yet been shown for banana despite its importance as a cash and food crop in tropical regions, although bananas are sensitive to aluminium stress. We studied the effects of the arbuscular mycorrhizal fungus Glomus intraradices in alleviating aluminium toxicity in the banana cultivar Grande Naine grown in a continuous-nutrient-flow cultivation system using dilute solution. The micropropagated plants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 45 publications
4
23
0
4
Order By: Relevance
“…Accumulation/sequestration in fungal structures has been demonstrated earlier [8,14] and hypothesised for toxic elements such as aluminium [15]. Fixation on extramatrical binding sites, sequestration within extraradical mycelium or intraradical structures i.e.…”
Section: Ecorad 2001mentioning
confidence: 84%
“…Accumulation/sequestration in fungal structures has been demonstrated earlier [8,14] and hypothesised for toxic elements such as aluminium [15]. Fixation on extramatrical binding sites, sequestration within extraradical mycelium or intraradical structures i.e.…”
Section: Ecorad 2001mentioning
confidence: 84%
“…In addition, the residual Al concentrations and total Al concentrations showed a significant decrease after planting S. cumini plantation onto the shale dump, which suggests that S. cumini tree species is effective for amending the Al contaminated soils. AM fungi have been reported to be effective in alleviating Al toxicity to plants by enhancing the nutrient and water acquisition in metal-contaminated soils although it may not degrade the metal toxicity directly (Clark 1997;Meharg and Cairney 2000;Rufyikiri et al 2000;Wu 2008). Planting trees associated with mycorrhizal fungi seems to be a robust and promising bioremediation strategy for many polluted soil sites (Banitz et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The metal of greatest concentration in oil shale waste is Al ([1,000 mg kg -1 ) with small amounts of As, Cr, Cd, Pb, Ni, Mn, Zn and Cu (Xia et al 2004). Aluminum toxicity is a major growth-limiting factor for crop cultivation in acid soils and many studies have demonstrated the suppressive effects in different plant species of soluble Al on root and shoot growth and water and nutrient uptake (Kochian 1995;Clark 1997;Rufyikiri et al 2000). In addition, soil microorganisms or nematodes were more sensitive than roots as indicators of subtle chemical changes in soil or water solution with Al toxicity (Williams and Dusenbery 1990;Joner et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The banana plant is a model case study since this plant is very sensitive to Al stress (Rufyikiri 2000a(Rufyikiri , 2000b and it exhibits very large K requirements and growth rate (Lahav, 1995), as well as selective root uptake of NH 4 . Thus banana plant has a high potential for acidifying its own rhizosphere, and thereby in solubilizing toxic forms of Al.…”
Section: Bananamentioning
confidence: 99%
“…In monoxenic cultivation, Rufyikiri et al (2000a) show that arbuscular mycorrhizal (AM) fungi (Glomus intraradices) can be effective in alleviating the aluminium toxicity to banana plants. In that study, both banana plants and AM fungi grew very well in sand under continuous nutrient flow.…”
Section: Bananamentioning
confidence: 99%